A systematic design guideline on wayfinding signage at a public hospital in Malaysia / Nur Faizah Mohd Pahme - Mohd Pahme, Nur Faizah (2022)
Wayfinding-signage is used to direct a person to a certain place with the guidance of visual assistance. In which, wayfinding is essential to mobility and stimuli the users especially the visitors and patients of public hospital to be navigated to the intended destinations. Whereby, their capacity for wayfinding is being affected by physiological and psychological decrements. Researcher has found out that lack of functional wayfinding-signage design used at public hospital has become an issue to this research. Hence, it assisted the researcher to obtain the research aim by recommending the systematic design guideline on wayfinding-signage for the visitors and patients of public hospitals in Malaysia. The research study was conducted in three stages of the research process.